2018
DOI: 10.1097/pas.0000000000001090
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Algorithmic Proposal Based on Comprehensive Immunohistochemical Evaluation of 297 Invasive Endocervical Adenocarcinomas

Abstract: The International Endocervical Adenocarcinoma Criteria and Classification was developed to separate endocervical adenocarcinomas (ECAs) into 2 main categories on the basis of morphology such as human papilloma virus-associated (HPVA) and non-human papilloma virus-associated adenocarcinomas. We aimed to improve the diagnostic accuracy of International Endocervical Adenocarcinoma Criteria and Classification by performing a comprehensive immunohistochemical evaluation and constructing objective immunohistochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
111
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 58 publications
8
111
2
3
Order By: Relevance
“…Diagnostic criteria for ADC histological types were established as per the 2014 WHO classification 2 and the International Endocervical Adenocarcinoma Criteria and Classification (IECC) system. 3,13 For this study, 201 cases of U-EAC and 12 cases of GAC were included; the remaining 11 cases of other histological types of ADCs (clear cell carcinoma, 7 cases; mesonephric carcinoma, 1 case; serous carcinoma, 1 case; endometrioid carcinoma, 2 cases) were excluded. This study was approved by the Institutional Ethics Board at Xijing Hospital.…”
Section: Patientsmentioning
confidence: 99%
“…Diagnostic criteria for ADC histological types were established as per the 2014 WHO classification 2 and the International Endocervical Adenocarcinoma Criteria and Classification (IECC) system. 3,13 For this study, 201 cases of U-EAC and 12 cases of GAC were included; the remaining 11 cases of other histological types of ADCs (clear cell carcinoma, 7 cases; mesonephric carcinoma, 1 case; serous carcinoma, 1 case; endometrioid carcinoma, 2 cases) were excluded. This study was approved by the Institutional Ethics Board at Xijing Hospital.…”
Section: Patientsmentioning
confidence: 99%
“…GAS is characterised as negative for p16 INK4a , oestrogen receptor, and progesterone receptor, and positive for p53 (mutant pattern), hepatocyte nuclear factor‐1β, carbonic anhydrase type IX, PAX8, and a variety of gastric markers . An algorithmic approach to the diagnosis of GAS with a panel of antibodies has been proposed . Asaka et al .…”
Section: Gastric‐type Adenocarcinoma: Expansion Of the Category Beyonmentioning
confidence: 99%
“…47,51,53,54 An algorithmic approach to the diagnosis of GAS with a panel of antibodies has been proposed. 55 Asaka et al recently demonstrated the diagnostic utility of Trefoil factor family 2 protein, which is a novel sensitive and specific gastric marker. 56 It should be kept in mind that p16 INK4a can be positive, and diffuse positive staining does not necessarily implicate high-risk HPV in pathogenesis, and does not exclude GAS.…”
Section: Gastric-type Adenocarcinoma: Expansion Of the Category Beyonmentioning
confidence: 99%
“…For example, Park et al reported that only 9% of their gastric‐type EA cohort showed diffuse positivity for HIK1083, and Carleton et al showed that whereas MUC6 expression was seen in 81% of their gastric‐type EAs, diffuse staining was present in only 35% of positive cases . In addition, p53 may also show a mutation‐type pattern (strong, diffuse expression or complete lack of expression) in up to 50% of the cases . Oestrogen and progesterone receptor staining is most commonly negative .…”
Section: Introductionmentioning
confidence: 99%
“…13 In addition, p53 may also show a mutation-type pattern (strong, diffuse expression or complete lack of expression) in up to 50% of the cases. 13,17 Oestrogen and progesterone receptor staining is most commonly negative. 13 Also of note is that gastric-type EAs have been reported to express napsin A and hepatocyte nuclear factor 1b, which are markers typically associated with the diagnosis of clear cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%